Radioprotective role of amifostine on osteointegration of titanium implants in the tibia of rats - Aydemir Celep, Nevra; Kara, Hülya; Erbaş, Elif; Doğan, Elif (XMLink, 2023)
Titanium is the most widely used metal for bone integration, especially for cancer patients receiving ionizing radiation. This study aimed to investigate the amifostine administration that would reduce the effects of radiation on bone healing and osseointegration in rat models.It is aimed that the application of amifostine in rats receiving radiotherapy treatment will reduce the negative effects of ionizing radiation on the bone.Thirty-five adult male Wistar rats were randomly divided into one healthy and four experimental groups. In three consecutive days, two experimental groups of rats (AMF-RT-IMP and RT-IMP) were exposed to radiation (15 Gy/3 fractions of 5 Gy each). Then the titanium implants were inserted into the left tibia. Before the radiotherapy process, a 200 mg/kg dose of amifostine (AMF) was administered to the rats in the AMF-IMP and AMF-RT-IMP groups. Twenty-eight days after the screw implant, all rats were sacrificed, and their blood samples and tibia bones were collected for analysis.The results indicated an accelerated bone formation and a more rapid healing process in the screw implants in the AMF-IMP, AMF-RT-IMP, and AMF-RT groups than in the RT-IMP group. Also, bone-implant contact area measurement and inflammation decreased with amifostine treatment in the implants subjected to irradiation (p < 0.05).The results obtained in the present study suggested that amifostine prevents the losses of bone minerals, bone integrity, and implant position from ionizing-radiation when given before exposure.
Keywords: Male; Titanium; Amifostine; Tibia; Animals; Original Article; Radiation-Protective Agents; Rats, Wistar; Rats; 3. Good health